Hypoxia inducible factor 1α and 2α overexpression in inflammatory bowel disease. Issue 3 (1st March 2003) - Giatromanolaki, A; Sivridis, E; Maltezos, E; Papazoglou, D; Simopoulos, C; Gatter, K C; Harris, A L; Koukourakis, M I
Abstract : Aims: Hypoxia inducible factors 1α and 2α (HIF1α and HIF2α) are hypoxia regulated transcriptional factors, which control the expression of a variety of genes responsible for angiogenesis, glycolysis, and the inhibition of apoptosis. Because angiogenesis and tissue regeneration are integral components of the inflammatory process, this study was designed to investigate the role of HIFα molecules in inflammatory bowel disease. Methods: Surgical specimens from patients with active ulcerative colitis (UC) and Crohn's disease (CD) were assessed immunohistochemically for HIF1α and HIF2α reactivity, and the expression of these molecules was compared with the expression of the angiogenic factors thymidine phosphorylase (TP), vascular endothelial growth factor (VEGF), and VEGF–KDR activated vasculature. The vascular density of the lesions was also assessed using anti-CD31 immunostaining. Results: HIF1α was expressed focally (epithelial cells, stromal fibroblasts, and myocytes) in both UC and CD, whereas HIF2α was expressed focally in UC and diffusely in CD. TP expression was uniformly positive in both diseases. VEGF expression was absent in CD, and weakly positive in UC. The VEGF–KDR reactivity of the submucosal vasculature was only slightly increased in UC and CD compared with normal tissue. The inflammatory cells stained with HIF2α and TP in all cases, but the reactivity was generalised in CD and focal in UC. In both diseases, vascular density was significantly higher than that seen in normal tissue. Conclusions: The discordant expression of HIF2α and VEGF in CD suggests an inherent deficiency of the intestine to respond to various stresses by the induction of VEGF. This finding should be investigated further.